Dimensi Wellness dalam kaitan dengan Kualitas Hidup Lansia di Indonesia - Asvi Retty Nurgusmy Yerly Asir; Lili Indrawati; Dinni Agustin; Tri Budi W Raharjo (LPPM Universitas Respati Indonesia, 2022)
An increasing number of elderly with chronic degenerative diseases and disabilities will affect their quality of life.The study design was cross-sectional in the form of case studies and evaluations in three areas of caregiving. Clinical diagnosis used geriatric assessment instruments of Geriatric Division of Cipto Mangunkusumo Hospital. Measurement of quality of life used the EQ-5D index score Indonesia version with 0,692 cut-off point for low and high quality of life.Quality of life of elderly living in the community is better than staying at home. There were habit of doing health checks, grateful, social activities, mutual friendship, participation in / outside environment, remain employed significantly associated with quality of life of the elderly. Relationship with quality of life of contextual factors obtained employment status, and number of disease was significantly correlated with quality of life, whereas cognitive function meaningful trend.It turns out that the quality of life of elderly living in the community is better than staying at home.